Identification of novel compound heterozygous variants in the DNAH1 gene of a Chinese family with left-right asymmetry disorder - Yuan, Lamei; Yu, Xuehui; Xiao, Heng; Deng, Sheng; Xia, Hong; Xu, Hongbo; Yang, Yan; Deng, Hao (Frontiers in Molecular Biosciences, 2023)
Most internal organs in humans and other vertebrates exhibit striking left-right asymmetry in position and structure. Variation of normal organ positioning results in left-right asymmetry disorders and presents as internal organ reversal or randomization. Up to date, at least 82 genes have been identified as the causative genetic factors of left-right asymmetry disorders. This study sought to discover potential pathogenic variants responsible for left-right asymmetry disorder present in a Han-Chinese family using whole exome sequencing combined with Sanger sequencing. Novel compound heterozygous variants, c.5690A>G (p.Asn1897Ser) and c.7759G>A (p.Val2587Met), in the dynein axonemal heavy chain 1 gene (DNAH1), were found in the proband and absent in unaffected family members. Conservation analysis has shown that the variants affect evolutionarily conserved residues, which may impact the tertiary structure of the DNAH1 protein. The novel compound heterozygous variants may potentially bear responsibility for left-right asymmetry disorder, which results from a perturbation of left-right axis coordination at the earliest embryonic development stages. This study broadens the variant spectrum of left-right asymmetry disorders and may be helpful for genetic counseling and healthcare management for the diagnosed individual, and promotes a greater understanding of the pathophysiology.